1980
DOI: 10.1111/j.1524-4725.1980.tb00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Subungual Exostosis: Treatment as an Office Procedure

Abstract: The authors describe a series of 49 patients with subungual exostoses, four of them in fingers, the rest in the toes. They present a new and simple technique of extirpation that can be done as an office procedure and with immediate restoration of function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The population in this study is similar to that reported in others 1 , 2 , 6 . In the two largest series, Oliveira et al 7 . found the big toe to be affected in 35 of 49 (71%) and Landon et al 1 .…”
Section: Discussionsupporting
confidence: 89%
“…The population in this study is similar to that reported in others 1 , 2 , 6 . In the two largest series, Oliveira et al 7 . found the big toe to be affected in 35 of 49 (71%) and Landon et al 1 .…”
Section: Discussionsupporting
confidence: 89%
“…This topic is underrepresented in the orthopaedic literature, because many of the important clinical series have been published in journals from other specialties [4,8,9,12,15,20,21,29,30,33,34,41], reflecting the fact that the condition is treated by many kinds of nonorthopaedic providers. Complete marginal excision of the exostosis appears to mitigate recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Neither radiation nor simple cautery is effective (35). One large series achieved good results with a specific surgical procedure (19). Briefly, the nail plate was avulsed after a local anesthetic block was given.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that the lesion be saucerized as it tology (7,351. can recur if this is not done (15,22,35). Various authors reported from 5% to 11% recurrence after excision and curettage (19,35). In all patients subsequent reexcision was effective.…”
Section: Discussionmentioning
confidence: 99%